Integrating microfluidics and biosensing on a single flexible acoustic device using hybrid modes. Issue 5 (6th February 2020) - Tao, Ran; Reboud, Julien; Torun, Hamdi; McHale, Glen; Dodd, Linzi E.; Wu, Qiang; Tao, Kai; Yang, Xin; Luo, Jing Ting; Todryk, Stephen; Fu, Yongqing
Abstract : A flexible thin film acoustofluidic device generates hybrid wave modes for microfluidic actuation (Lamb waves) and biosensing (thickness shear waves). Abstract : Integration of microfluidics and biosensing functionalities on a single device holds promise in continuous health monitoring and disease diagnosis for point-of-care applications. However, the required functions of fluid handling and biomolecular sensing usually arise from different actuation mechanisms. In this work, we demonstrate that a single acoustofluidic device, based on a flexible thin film platform, is able to generate hybrid wave modes, which can be used for fluidic actuation (Lamb waves) and biosensing (thickness shear waves). On this integrated platform, we show multiple and sequential functions of mixing, transport and disposal of liquid volumes using Lamb waves, whilst the thickness bulk shear waves allow us to sense the chemotherapeutic Imatinib, using an aptamer-based strategy, as would be required for therapy monitoring. Upon binding, the conformation of the aptamer results in a change in coupled mass, which has been detected. This platform architecture has the potential to generate a wide range of simple sample-to-answer biosensing acoustofluidic devices.